A framework of biomarkers for brain aging: a consensus statement by the Aging Biomarker Consortium - Jia, Yu-Juan; Wang, Jun; Ren, Jun-Rong; Chan, Piu; Chen, Shengdi; Chen, Xiao-Chun; Chhetri, Jagadish K; Guo, Junhong; Guo, Qihao; Jin, Lingjing; Liu, Qiang; Liu, Qiang; et al. (Life medicine, 2023)
Abstract China and the world are facing severe population aging and an increasing burden of age-related diseases. Aging of the brain causes major age-related brain diseases, such as neurodegenerative diseases and stroke. Identifying biomarkers for the effective assessment of brain aging and establishing a brain aging assessment system could facilitate the development of brain aging intervention strategies and the effective prevention and treatment of aging-related brain diseases. Thus, experts from the Aging Biomarker Consortium (ABC) have combined the latest research results and practical experience to recommend brain aging biomarkers and form an expert consensus, aiming to provide a basis for assessing the degree of brain aging and conducting brain-aging-related research with the ultimate goal of improving the brain health of elderly individuals in both China and the world.